Dampak Pandemi Covid-19 Terhadap Kinerja Dosen UNAI Pada Tahun Ajaran 2019/2020 - Albinur Limbong (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2021)
This paper is a report of a study about the impact of covid-19 pandemic onto the performance of faculties in Universitas Advent Indonesia in academic year 2019/2020. The purpose of this study is to see whether covid-19 pandemic influence teacher performance indicated by the students’ evaluation. The population of the study is all lecturers in UNAI who taught during the odd and even semester 2019/2020, i.e. 91 lecturers. The questionnaire consists of 33 questions involving 5 basic competences of teacher, namely pedagogic (9 items), professional (8 items), personality (6 items), social (5 items) and spiritual (5 items). The teacher performance is analysed using t-test or anova statistical analysis based on faculty, age, gender, and degree. The analysis indicated that (1) there is a significant difference in teacher performance among the faculties, (2) there is significant difference in teacher performance based on age, gender and degree held. This analysis indicated that the covid-19 pandemic does not have any significant impact onto the teacher performance. The difference in the teacher performance among the faculties (departments) may not be due to covid-19 pandemic, since it also occurred before the pandemic. For study the pandemi occurred about 2.5 months, or half semester, since in the middle of March 2020, therefore it is interesting to do a further study whether a long term pandemic has an impact on the teacher performance if the online learning continues.